Biodiversity and Distribution of Brachyuran Crabs Along the Chennai Coast, Tamil Nadu, India - Jayaprakash, Jayanthi; Jacob, Akil; Ranjitha, Jeevanandam; Ragunathan, Manickavalli Gurunathan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Biodiversity encompasses all living organisms including plants, microorganisms, animals, and people. It refers to the abundance of a species and can be applied specifically to all species found in a particular area or environment. A healthy ecosystem supports a wide variety of lives, whereas a lack of biodiversity can indicate environmental issues, such as contaminated water or air. The Chennai marine ecosystem experiences many anthropogenic activities. This study examined the diversity of brachyuran crab species in the Chennai marine ecosystem at nine different stations, extending from Ennore in the north to Uthandi in the south. The significant result of this study is that it focuses on their taxonomy and range, revealing 11 families and 29 species of brachyuran crabs in the Chennai region. This study marks the first attempt to revisit the taxonomy of Brachyuran crabs along the coast of Chennai.